The Extent of Informed Decision-Making about Starting Dialysis: Does Patients’ Age Matter? - Song, Mi-Kyung (2014)
BACKGROUND: A growing number of elderly patients with end-stage renal disease start dialysis. We examined elderly (≥ 65 years) patients’ views about their decision-making experience after starting dialysis in comparison with patients aged 50-64 years, and patients ≤ 49 years. METHODS: Ninety-nine patients from 15 outpatient dialysis centers in North Carolina, USA completed a semi-structured interview asking them about the context of decision-making and their decision-making experience, and a 10-item investigator-developed Informed Decision-Making (IDM) questionnaire with binary response options (yes/no). RESULTS: While IDM scores were low for all three groups (< 5 out of 10), they were significantly lower for the older group compared to the other two younger groups (p = 0.02). A significantly lower percentage of the older group said that the doctor explained underlying conditions that led to kidney failure (p = 0.04), the impact of dialysis on daily life (p = 0.04), and the life-long need for dialysis (p < 0.01), and that the doctor tried to make sure the patient understood the information (p = 0.01). Also a significantly higher percentage of elderly patients felt the decision was made by the doctor rather than on their own or with their family, or collaboratively with the doctor (p = 0.04). CONCLUSIONS: Informed decision-making is significantly poorer in patients aged 65 years or older than in younger patients. Clinicians should communicate clearly about the benefits and burdens of dialysis to older adults and provide an opportunity for them to understand the significant trade-offs that dialysis may require.